2021
DOI: 10.1101/2021.10.28.21265608
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Social discrimination and stigma on the community of health professionals during the Covid-19 pandemic. An ethnographic approach

Abstract: Severe Acute Respiratory Syndrome Coronavirus Type 2 (SARS-CoV-2) that caused the pandemic since March 2020, has affected among others, health professionals who work in covid-19 units by facing social discrimination. The aim of this study was to record the experiences of health professionals working in the first line of treatment of the pandemic, to analyse the effects of the pandemic on the interpersonal relationships of health professionals, and to ask about the stigma they faced during their work with peopl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 26 publications
1
1
0
Order By: Relevance
“…In the following questions about their intention to build strong relationships with a diverse community, the participants show that they evaluate themselves highly and state that they have acquired the cultural ability to a significant degree without facing any difficulties or problems. Other studies come to similar conclusions [ 23 ].…”
Section: Discussionsupporting
confidence: 79%
“…In the following questions about their intention to build strong relationships with a diverse community, the participants show that they evaluate themselves highly and state that they have acquired the cultural ability to a significant degree without facing any difficulties or problems. Other studies come to similar conclusions [ 23 ].…”
Section: Discussionsupporting
confidence: 79%
“…In the Community Health Care context, one of the most important issues discussed among experts is health promotion and the prevention of diseases of specific population groups characterized by risk factors. As there has been such a huge outbreak of awareness programs for the COVID-19 pandemic crisis, it would be useful to extend similar programs to other diseases that affect the health of communities over time [ 3 ].…”
Section: Round 1 Reviewmentioning
confidence: 99%
“…Therefore, they have been seen the people threatening active social life and facing social exclusion. Argyriadis et al (2021) found in their study aiming to examine social exclusion experienced be healthcare professionals during the pandemic that families of nurses approached them with fear and hesitation during face-to-face conversations and this made them feel bad. In addition, nurses stated that their close environment tended to avoid them (Argyriadis et al, 2021, pp.1-27).…”
mentioning
confidence: 99%